User Interface and User Experience Design for Character Development System Web Application at State Vocational School 56 Jakarta Based on Prototypes with The User Centered Design Method - Miftahudin Rifki; Verdi Yasin; Anton Zulkarnain Sianipar (Universitas Mohammad Husni Thamrin, 2026)
In the digital era, information technology plays a crucial role in supporting various activities, including education. One increasingly developed technology implementation is a web-based student violation recording system. This system not only simplifies the process of recording and monitoring violation data but can also be integrated with student character development programs. At SMK Negeri 56 Jakarta, character development is a crucial part of the educational process, but its implementation still faces various challenges, particularly regarding the effectiveness and efficiency of digital data recording. This research aims to design the User Interface (UI) and User Experience (UX) for a prototype-based character development system web application using the User-Centered Design (UCD) method. This method is used to ensure that the application design truly centers on the needs of the user, in this case the Student Affairs Team. Through this approach, the application is expected to present an easy-to-use, engaging interface and provide a positive user experience. The result of this research is a web application prototype design that can display historical student violation data, facilitate the development process more efficiently, and present interactive data visualizations to assist the school in analyzing student character development. Therefore, this application is expected to support the increased effectiveness of character development at SMK Negeri 56 Jakarta and become a digital solution that adapts to the needs of modern education.